2017
DOI: 10.1089/pho.2016.4215
|View full text |Cite
|
Sign up to set email alerts
|

Does Low-Level Laser Therapy Enhance the Efficiency of Orthodontic Dental Alignment? Results from a Randomized Pilot Study

Abstract: The results of this pilot study suggest that the administration of LLLT might significantly increase the efficiency of orthodontic treatment during dental alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 27 publications
3
63
2
Order By: Relevance
“…In the present study, the greater expansion obtained on the crossbite side could also be attributed to the accelerated periodontal response induced by LLLT. 12,13,17 In this respect, it has been demonstrated that LLLT accelerates cellular turnover by increasing vascular activity and the availability of ATP, stimulates proliferation of osteoblasts, increases fibronectin and collagen I levels, and stimulates fibroblast growth and proliferation. [12][13][14]18,19 In the orthodontic field, the assumption is that such increased cellular metabolic activity can speed the rate of bone remodeling, as recently demonstrated by clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, the greater expansion obtained on the crossbite side could also be attributed to the accelerated periodontal response induced by LLLT. 12,13,17 In this respect, it has been demonstrated that LLLT accelerates cellular turnover by increasing vascular activity and the availability of ATP, stimulates proliferation of osteoblasts, increases fibronectin and collagen I levels, and stimulates fibroblast growth and proliferation. [12][13][14]18,19 In the orthodontic field, the assumption is that such increased cellular metabolic activity can speed the rate of bone remodeling, as recently demonstrated by clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,17 In this respect, it has been demonstrated that LLLT accelerates cellular turnover by increasing vascular activity and the availability of ATP, stimulates proliferation of osteoblasts, increases fibronectin and collagen I levels, and stimulates fibroblast growth and proliferation. [12][13][14]18,19 In the orthodontic field, the assumption is that such increased cellular metabolic activity can speed the rate of bone remodeling, as recently demonstrated by clinical trials. 12,17 We installed the palatal expander on the same day of the surgical procedure, thus no latency period was planned between corticotomy and the beginning of orthodontic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations